A rare presentation of Y-duplication of the pancreatic tail with enteric duplication cyst as intussusception in a child: A case report. (January 2021) - Banerjee, Rupa; Singh, Gaurav; Aggarwal, Satish K.
Highlights: Duplication cysts can occur anywhere in the gastrointestinal tract but duplication cyst within the pancreas is rare. The most common presentation reported is abdominal pain secondary to pancreatitis. The present case presented with abdominal pain, non-bilious vomiting and ill-defined lump in the left lumbar region. USG showed a target sign and intussusception was suspected. At operation, there was a thick-walled cyst in relation to tail of pancreas, covered with necrotic omentum. Histology confirmed enteric gastric duplication. Abstract: We report a case of a 2-year-old girl who presented to us with complaints of pain abdomen and non-bilious vomiting. USG was suggestive of intussusception with necrotic bowel and free fluid in the left lumbar region. Operative findings were of enteric duplication cyst of the pancreas which was later confirmed on histopathology. Enteric duplication cysts can occur anywhere in the gastrointestinal tract but duplication cyst within the pancreas is rare. The most common presentation in other reported cases is pain abdomen due to pancreatitis but in our case, we had findings of intussusception. Children usually present with a severe complication like perforation of duplication cyst as in our case. Excision of the cyst and the duplicated pancreatic tail is the mainstay of treatment.